The visual essay: rethingking communications from Hybridity - Marquina Vega, Orietta (2018)
This article reflects on visual essay as a research instrument within social communication, which builds meaning from the visual, linking ideas, emotions and affects, and contributes to build an inclusive public sphere at the service of the public good, within visual culture. Its hybrid nature intertwines visual and verbal language, which, unlike other visual and audiovisual products, allows argumentation and to build a thought that includes subjectivity, but also to the Other. It is from this relationship with the Other that proposes a way of learning and interacting with reality as something different, according to sensitivities that aestheticization of social communication demands, and obtains its truth from the intersubjectivity with which it is constructed.